MSN Approach Model in the Implementation of Waste Management Policy in Bungo District - Hamirul, Hamirul; Hidayat, Nanang Al; Poiran, Poiran (Sebatik, 2024)
This research is motivated by the increasing volume of waste in the Market Village, where the waste collection fleet cannot transport waste daily, especially in residential areas of Pasir Putih Village and Batang Bungo Village. The aim of this study is to develop a recommendation model using the MSN (Mentality, System, Networking) approach for the implementation of waste management policies in Bungo Regency, with a focus on Pasir Putih Village and Batang Bungo Village. This research employs a descriptive method with a qualitative approach. The findings indicate improvements in attitudes, behaviors, and responsibilities among policy stakeholders, categorized under the Mentality Approach. The organizational structure and functions related to implementing waste management policies across the Kelurahan in Rimbo Tengah and Market sub-districts were found to be relatively effective, falling under the System Approach. However, in terms of synergy, there is a need to enhance institutional collaboration, policy programs and budgeting, human resources, data management, and monitoring and evaluation strategies. For the symbiotic mutualism aspect, it is essential to base efforts on the principles of mutual need, mutual benefit, and mutual support. The Networking Approach analysis reveals that strategic partnerships in waste management are still not functioning effectively.